(untitled) (Foro de Educacion, 2026)
Drama education in higher learning is not only performance training, but it also has immense prospects of enhancing the psychological well-being, social skills, and creative thinking among the students. However, the current literature has given little attention to its other developmental benefits, despite its artistic and pedagogical roles. This gap is addressed in the paper through a Systematic Literature Review (SLR) that explores how drama education affects psychosocial and cognitive evolution. The systematic review implied the discussion of 16 peer-reviewed articles published in 2015-2025 according to PRISMA rules, with the assistance of different educational and cultural backgrounds. The three core areas of the drama-based learning in the review suggest the same similar pattern, namely, increased emotional regulation and self-awareness; increased levels of communication, empathy and social interaction; and creative thinking and problem-solving capabilities. Such information forms a picture of drama education as a powerful and multidimensional tool of all-round student development. According to the study, the issue of change in the sphere of higher education is required, and drama should be viewed as a valuable element of academic research. It also highlights the importance of interdisciplinary strategies that relate drama to mental health, social learning and innovation. Lastly, the given research relocates drama education as a valuable means of individual and educational growth in universities.